(untitled) (Journal of the College of Education for Women, 2019)
This study has contributed to identify convenience of the land Usifiya of Mahmudiya district baghdad province for the cultivation of sensitive and salt resisting crops and growing pasture .The nine pedons (tracks) of the study have spread over three transects to cover the whole area the north, middle and south .Depending on Visual Space tupe (TM) for 2007 which is super classified, samples are distributed on all classes of land coverIt is detected the presence of nine series soils namelyMM5- MW96- DM 115 for 1st transectMF12- DM46 - DM96 for 2nd transectDM56- DF56 - MW5 for 3rd transectSoils are classified to the level of sub great group according to (soil Survey Staff) to :*Typic Torri Fluvents , Typic HaplosaldsSome properties of soil including chemical are choosen, which determine the degree and the optimal convenience of the land, using the method of standard beating (Sys 1980) These are soil texture clalcium carbonate Gypsum , salinity drainage state Exchangable sodium Ration, soil depth, horizon development and weathering index.Results show that by application of the equation there are five varieties suitable for cultivation for each kind of crops :-A. For sensitive crops :-very suitable S1 : it include series DW96 with11.1%, suitable S2 : series MW5 & DM56 with 22.2 % medium suitable S3: series DM115 – MM5 – DM96 with 33.3 %Less suitable S4 : series DM46 with 11.1 %, insuitabhe N : series DF56 with 11.1%B. for resisting crops :Very suitable S1 : it includes series DW96 _ MW5 _ DM56 with 33.3 %Suitable S2 : series DM115 _ MM5 _ DM96 with 33.3%Medium suitable S3 : series DM46 with 11.1 %Less suitable S4 : series DF12 with 11.1%Insuitable N : series DF56 with 11.1 %c)for grain for Dqsture :very suitable S1 : it include series DM56_ MW5 _ MM5 with 33.3%suitable S2 : series DM96 _ DM96 _ DM115 with 33.3 %medium suitable S3 : series DM46 with 11.1 %less suitable S4 : series MF12 with 11.1 %insuitable N: it include series DF56 with 11.1 %The area of each class of suitable varieties of different crops has been specified using the program Arc GiS10.2 with the help of geostat istics Analysis .The area of different types are :-Sensitive crops, S1: 16.79 km2 , S2: 89.15 km2 , S3: 248.3 km2 , S4 : 37.18 km2 , N : 18.00km2 . Salt – resisting crops , S1: 180.14 km2 , S2: 182.82 km2 , S3:28.29 km2, S4: 11.19km2 , N:6.91 km2 . grain for pastuer , S1: 224.59km2 , S2 : 127.77 km2 , S3:38.77 km2 , S4 : 12.44km2 , N : 5.88 km2 .